Social Dimensions of Education in the Era of the Internet of Things (IoT) and COVID-19 Pandemic - Sabam Parjuangan; Meliyanti Meliyanti (Journal of Asian Social Science Research, 2021)
Internet of things (IoT) brings disruption to services in society including education. New platforms in educational services made possible by the internet of things have changed the way of teaching and learning activities. The question was how schools provide services to their stakeholders. This disruption was accelerated with the onset of the COVID-19 pandemic. This article aims to identify the social dimensions of education and their characteristics caused by the disruption of IoT technology and COVID-19. It examines social dimensions from the point of view of social intelligence, which comprises of three dimensions, namely social sensitivity, social insight, and social communication. In doing so, this study used a qualitative method based on a survey that involved respondents and their experience of learning through the IoT platforms. The results of this study indicate that social sensitivity and social communication were the most problematic social dimensions in learning and teaching activities through the IoT platforms. On the other hand, social insight was a very good dimension experienced by students in learning and teaching activities through IoT and during the COVID-19 pandemic.